PEMANFAATAN LIMBAH BATUBARA (FLY ASH) UNTUK BAHAN STABILISASI TANAH DASAR KONSTRUKSI JALAN YANG RAMAH LINGKUNGAN - Zuraidah Jauhari; Achmad Fauzi; Usama Juniansyah Fauzi (Jurnal Tekno Global, 2018)
Now days, Indonesia gets much the using of coal as alternative energy  because increased of oil price and increased  demand  in the  country. The expected production of coal in 2010 at about 230  million tons, where  68.5 million tons for local needs (45-46 million tons for electric power plant). Sumatera Selatan province is one of coal resources province in Indonesia and also has electric power plant have to promoted the utilizing of polluted material from electricity power plant. Industry electric coal power plant produced 5% polluted  as fly ash and bottom ash, where 10-20% as bottom ash and as 80-90% fly ash. That polluted  can be utilized as additives material   in soil stabilization for road construction.  This publication proposes an assessment of the utilization of lime, Portland cement (PC), fly ash as stabilizer of soft sub grades material in highway construction. The research conducts various contents of fly ash to different types of clay soils from various sites in Kuantan. The compaction tests and California Bearing Ratio (CBR) tests were applied in soil samples to estimate the optimum mixture design. The samples were set up by mixing soil samples with various content of fly ash and at optimum water content. The accomplishment of sub-grade stabilization depends on the engineering properties of soils and characteristic of additives. The laboratory result shows that the strength gain in stabilization mainly depends on two factors: additives content and molding water content. The variation content of fly ash and were 4%, 8% and 12% by total weight.Keywords: Sustainable, Engineering Properties of Soil, Soil Stabilization, CBR